Prevalence of Vitamin B12 Deficiency In Patients With Type II Diabetes Mellitus On Metformin - Malla, D.; Bajracharya, M.R.; Karki, B.B.; Rajouria, A.D.; Shrestha, P.S. (Journal of Diabetes and Endocrinology Association of Nepal, 2021)
Background: Diabetes Mellitus is one of the most encountered disease in our out patient department and metformin is the first drug of choice to treat Diabetes mellitus. As metformin is one of the cheapest drug, many patients use these drug for long period of time with consultation and without consultations with doctors. Patients under long term metformin use are not aware of Vitamin B12 deficiency and its associated signs and symptoms. In Nepal due to poverty, lack of education and awareness on diabetes mellitus we doctors find much difficult to explain patients on the consequences of diseases. So I decided to do this study which could be much easier to explain patients on effect of metformin of vitamin B12 levels and the consequences life style modifications and supplement of Vitamin B12 to the patients. Methods: This is a Cross-Sectional Study done in the patients with Type 2 diabetes were selected based on inclusion and exclusion criteria. Basic biochemical investigation were sent the lab of the National academy of medical science. Serum B12 assay were done. Vitamin B12 deficiency is defined as values <150pg/ml. Association between vitamin B12 deficiency with duration of metformin therapy, duration of diabetes, with age, sex were done. Results: The mean vitamin B12 level is low as the duration of metformin treatment increases. The sex, age relation with development of vitamin B12 deficiency was not significant. In my study out of 210 patients 107 patients were having severe vitamin B12 deficiency level and 63 patients had a borderline Vitamin B12 deficiency level which shows that the deficiency increases as per longer use of metformin, which shows prevalence of 50.95%. Conclusions: Vitamin B12 deficiency occurs in type 2 diabetes mellitus patients treated with long term metformin. The duration of metformin therapy significantly affects the development of vitamin B12 deficiency. As a treating physician we always need to explain our patients about the side effect of metformin and regular follow up and investigations must be done to early diagnosis of vitamin B12 deficiency to improve the quality of life.